KEBUDAYAAN DAN KEARIFAN LOKAL DI KAWASAN OBJEK WISATA DENAI LAMA, KABUPATEN DELI SERDANG - Ayu Fadhilla; Charles Faucold Nahampun; Masitoh Munthe; Mbina Pinem; Tumiar Sidauruk (Jurnal Samudra Geografi, 2022)
Abstract: The purpose of this research is to find out the culture and local wisdom in the Denai Lama Tourism Object Area and the activities that characterize the culture and local wisdom in the Denai Lama Tourism Object Area, Deli Serdang Regency. The method used in this study is a qualitative method, is a research and understanding process based on a methodology that investigates a social phenomenon and human problem. The data collection technique used in this study was carried out with the stages of observation and documentation of taking pictures directly in the area. The results of the study stated that, Denai Lama Tourism Village was the first Tourism Village in Deli Serdang Regency, at the initiative of the Head of the Youth, Sports, Culture and Tourism Office of Deli Serdang Regency. The principle of this tourist village is more about education, education, culture, culinary, so this is the main attraction of Kampong Lama village. So that one of the interesting spots in Denai Lama Village is Paloh Naga Tourism. This place is located on a hectare of rice fields, with photo spots that are quite interesting for visitors. There are also many characteristic activities, namely the existence of traditional culinary snacks, the existence of a folk party once a year, performing arts such as horse braids.